2022
DOI: 10.3389/fpls.2022.852704
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Suppresses Abscisic Acid, Modulates Antioxidant System to Counteract Arsenic-Inhibited Photosynthetic Performance in the Presence of Selenium in Mustard

Abstract: Arsenic (As) stress provokes various toxic effects in plants that disturbs its photosynthetic potential and hampers growth. Ethylene and selenium (Se) have shown regulatory interaction in plants for metal tolerance; however, their synergism in As tolerance through modification of the antioxidant enzymes and hormone biosynthesis needs further elaboration. With this in view, we investigated the impact of ethylene and Se in the protection of photosynthetic performance against As stress in mustard (Brassica juncea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 72 publications
(122 reference statements)
0
16
0
Order By: Relevance
“…Ethylene has long been documented as a significant modulator of plant stress responses by acting as a signaling chemical, primarily inhibiting ROS generation and strengthening the antioxidant defense system (Gautam et al, 2022; Khan et al, 2016; Rather et al, 2022; Sehar et al, 2021; Sehar, Iqbal, et al, 2022). In the present study, salt stress treatment increased ethylene production to a higher level, regarded as stress ethylene, together with a maximum glucose level that adversely impacted the growth and development of the plants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ethylene has long been documented as a significant modulator of plant stress responses by acting as a signaling chemical, primarily inhibiting ROS generation and strengthening the antioxidant defense system (Gautam et al, 2022; Khan et al, 2016; Rather et al, 2022; Sehar et al, 2021; Sehar, Iqbal, et al, 2022). In the present study, salt stress treatment increased ethylene production to a higher level, regarded as stress ethylene, together with a maximum glucose level that adversely impacted the growth and development of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of enzymes of the ascorbate‐glutathione cycle by ethylene have been shown earlier in plants under different stress environments (Fatma et al, 2021; Gautam et al, 2022; Jiang et al, 2018; Masood et al, 2012; Qin et al, 2008; Rather et al, 2022; Sehar et al, 2021; Wang et al, 2020). This improvement in photosynthetic efficacy attributed to the optimization of stress ethylene resulted in reduced ROS generation via enhanced antioxidant enzyme activity (Khan et al, 2016; Masood et al, 2012; Sehar et al, 2021; Sehar, Iqbal, et al, 2022). Prior reports demonstrated that melatonin treatment increased ethylene production in grapevine by promoting ACC synthesis via MYB108A expression (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations